Analysis of circulating tumour DNA to identify patients with epidermal growth factor receptor–positive non-small cell lung cancer who might benefit from sequential tyrosine kinase inhibitor treatment. (May 2021) - Provencio, Mariano; Serna-Blasco, Roberto; Franco, Fabio; Calvo, Virgina; Royuela, Ana; Auglytė, Milda; Sánchez-Hernández, Alfredo; de Julián Campayo, María; García-Girón, Carlos; Dómine, Manuel; Blasco, Ana; Sánchez, José M.; et al.
Abstract: Background: Survival data support the use of first-line osimertinib as the standard of care for epidermal growth factor receptor ( EGFR )–positive non-small cell lung cancer (NSCLC). However, it remains unclear whether upfront osimertinib is superior to sequential first- or second-generation tyrosine kinase inhibitors (TKIs) followed by osimertinib for all patients. It is impossible to predict which patients are at high risk of progression, and this constitutes a major limitation of the sequential TKI approach. Patients and methods: A total of 830 plasma samples from 228 patients with stage IV, EGFR -positive NSCLC who were treated with first-line TKIs were analysed by digital polymerase chain reaction (dPCR). Results: The circulating tumour DNA (ctDNA) levels helped to identify patients with significantly improved survival rate, regardless of the treatment. Patients treated with first- or second-generation TKIs (N = 189) with EGFR mutations in plasma at a mutant allele frequency (MAF) <7% before treatment initiation (low-risk patients) or who were ctDNA negative after 3 or 6 months of treatment and with an MAF <7% at diagnosis (high responders) had two-thirds lower risk of death than patients in the opposite situation (adjusted hazard ratio [HR] = 0.38; 95% confidence interval [CI]: 0.23–0.64 and HR = 0.22; 95% CI: 0.12–0.42, respectively). The median overall survival (OS) for low-risk patients and high responders treated with first- or second-generation TKIs was 34.2 months and not reached, respectively, regardless of second-line treatment. There were no significant difference in OS between low-risk or high-responder patients treated upfront with osimertinib (N = 39) and those treated under a sequential approach with osimertinib (N = 60). Median OS was not reached in both cases. Conclusions: Pre-treatment ctDNA levels identify low-risk patients, who may benefit from sequential TKI treatment. Information regarding EGFR mutation clearance can help to improve patient selection. Graphical abstract: Image 1 Highlights: It is yet unclear whether upfront osimertinib is the best approach for epidermal growth factor receptor–positive non–small cell lung cancer. Pre-treatment circulating tumour DNA (ctDNA) levels identify patients at low risk of progression and death. Negative ctDNA status after 3 or 6 months of treatment predicts a better prognosis. ctDNA clearance along with low baseline ctDNA levels identifies the group of best survival. Similar overall survival was observed among low-risk patients treated with first-line or second-line osimertinib.